Khomeini’s Concept of Wilâyat Al-Faqîh and Its Influence on the Contemporary Indonesian Islamic Thought - Bisri, Hasan (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
The concept of wilâyat al-faqîh from Imam Khomeini was one of the products of Islamic thought. It has revive discourse on Islamic studies in various parts of the Islamic world. It is not only become a threat to the status quo of the Muslim rulers, in fact it has been raising the academic and scholarly discussion in the forums of national, regional, and international levels. The influence of the concept of wilâyat al-faqîh from Imam Khomeini to contemporary Islamic thought in Indonesia looked on discourse about the relation between religion and state. Indeed, the debate on religion-state relations have long occurred in Indonesia, but in academic discourse becomes increasingly crowded since the concept of wilâyat al-faqîh serve as the basis for the establishment of the Islamic State of Iran by Imam Khomeini. Effect the concept of wilâyat al-faqîh in contemporary Indonesian Islamic thought encouraged by the publication of books by/about Imam Khoemini and about Shia in general and the development of Shi'i institutions in Indonesia.